Spectroscopic Study of EUV and SXR Transitions of Ba XLVI (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
An extensive set of energy levels, inverse radiative rates, wave-function composition in LSJ and JJ coupling schemes for the lowest 162 fine structure levels along with transition wavelengths, oscillator strengths, line strengths and transition probabilities for electric dipole (E1), magnetic dipole (M1), electric quadrupole (E2) and magnetic quadrupole (M2) EUV and SXR transitions from the ground state have been presented for Ba XLVI. For these calculations, the fully relativistic Multiconfiguration Dirac-Fock (MCDF) approach is employed. The QED corrections due to vacuum polarization and self-energy effects and Breit correction due to the exchange of virtual photons between two electrons are fully considered. To assess the authenticity and credibility of presented results, analogous calculations have also been performed by using a fully relativistic configuration interaction program (Flexible Atomic Code) based on self-consistent Dirac-Fock-Slater iteration method. Extreme Ultraviolet (EUV) and Soft X-ray (SXR) transitions are also identified. Comparison is also made with the available experimental and theoretical data. These accurate data are expected to be useful in fusion research and astrophysical investigations and applications.
Keywords: Energy levels; Transitions wavelength; Extreme Ultraviolet; Soft X-ray; Inverse radiative rates